Aquinas and Alison on Reconciliation with God - Sextro, Elizabeth (Lumen et Vita, 2018)
This paper compares the concept of reconciliation in the works of Thomas Aquinas and James Alison through a soteriological lens. For both authors, the problem of sin confronts humanity with grave implications for our salvation that cannot be fixed on our own; therefore, Christ must enact a new way for humanity to live in right relationship with God. The paper examines Thomas and Alison’s anthropologies through the lens of three questions regarding salvation: What does sin do to the human?; What does Christ have to do because of sin?; and finally, What does Christ enable humans to do in order that we may participate in reconciling ourselves to God?